2021
DOI: 10.21203/rs.3.rs-597657/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement of Entropy and Quantum Coherence Properties of Two Type-I Entangled Photonic Qubits

Abstract: Using the type-I SPDC process in BBO nonlinear crystal (NLC), we generate a polarization-entangled state near to the maximally-entangled Bell-state with high-visibility (high-brightness) 98.50 ±1.33 % (87.71 ± 4.45 %) for HV (DA) basis. We calculate the CHSH version of the Bell inequality, as a nonlocal realism test, and find a strong violation from the classical physics or any hidden variable theory (HVT), S= 2.71±0.10. Via measuring the coincidence count (CC) rate in the SPDC process, we obtain the quantum e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This type of NLC has potential to generate the type-II polarization-entangled Bell-state (for more details about the state of SPDC, see Refs. [2,8,9]).…”
Section: B Quasi-phase Matching (Qpm) Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…This type of NLC has potential to generate the type-II polarization-entangled Bell-state (for more details about the state of SPDC, see Refs. [2,8,9]).…”
Section: B Quasi-phase Matching (Qpm) Conditionmentioning
confidence: 99%
“…We are interested in measuring CHSH (Clauser, Horne, Shimony, and Holt) inequality [70] which is slightly different from the original Bell's inequality. In 1964, Bell showed that all hidden-variable theories (HVTs) obey his inequality, while quantum mechanics, for example entangled state, violates [8,67,68].…”
Section: Bell Inequality Measurement and Visibilitymentioning
confidence: 99%
See 2 more Smart Citations